Plague - Grant Michael 1954-; Michael Grant (New York : HarperCollins, 2014)
A deadly, flu-like epidemic and a plague of flesh-eating creatures threaten the lives of the children at Perdido Beach while Sam, Astrid, Caine, and Diana each struggle with doubts and uncertainties.
K
570